2011
DOI: 10.1016/j.gaitpost.2010.12.018
|View full text |Cite
|
Sign up to set email alerts
|

Body of evidence supporting the clinical use of 3D multisegment foot models: A systematic review

Abstract: Reported repeatability indices such as the coefficient of multiple correlation, standard deviation and standard error of measurement provide evidence for the continued use of 3DMFMs. While a number of published models exist, there is no adequate evidence available to support their clinical use. More reliability and validity studies are needed to confirm adequate measurement properties of 3DMFMs.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
86
0
3

Year Published

2013
2013
2023
2023

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 135 publications
(95 citation statements)
references
References 72 publications
4
86
0
3
Order By: Relevance
“…Several foot models, with a variable number of rigid bodies and degrees of freedom (DOF), have been proposed whose topological complexity varies essentially with the goal of the study [7]. Mono and two-segmental foot models are recurrent in literature [1][2][3], presenting high computational efficiency, however they are inefficient to analyze all the singularities that occur at ankle-foot and tarsus level.…”
Section: Introductionmentioning
confidence: 99%
“…Several foot models, with a variable number of rigid bodies and degrees of freedom (DOF), have been proposed whose topological complexity varies essentially with the goal of the study [7]. Mono and two-segmental foot models are recurrent in literature [1][2][3], presenting high computational efficiency, however they are inefficient to analyze all the singularities that occur at ankle-foot and tarsus level.…”
Section: Introductionmentioning
confidence: 99%
“…More recently, 3D multisegment foot models (3DMFMs) emerged allowing the quantification of the mobility of different foot segments during clinical gait analysis (Baker and Robb, 2006;Deschamps et al, 2011). The clinical usefulness of this method with respect to pathomechanical modelling has been underpinned with methodological as well as clinical studies in different patient populations (Deschamps et al, 2012a(Deschamps et al, , 2012bNess et al, 2008).…”
Section: Introductionmentioning
confidence: 99%
“…Additionally, foot morphological classifications were relatively broad and, whilst the potential for confounding variables is considered limited, no efforts to control for their occurrence were made. A likely explanation for the low correlation found between intersegmental JAs and sub-segmental vertical loading is that robust studies evaluating the repeatability of 3-D multi-segment kinematic foot models are yet to be reported (Deschamps et al 2011;Di Marco et al Forthcoming). This would suggest that any correlations that do exist between intersegmental kinematics and sub-segment loading would be obscured by the errors inherent in the measurement method.…”
Section: Resultsmentioning
confidence: 99%
“…These include studies of healthy adolescent gait (MacWilliams et al 2003), juvenile subjects with and without cerebral palsy (Stebbins et al 2005) and diabetic subjects (Hastings et al 2010;Deschamps et al 2011;Sawacha et al 2012). The most comprehensive investigation of the correlates between sub-area foot loading and joint kinematics was performed by Giacomozzi et al (2014), who found sagittal plane kinematics and baropodometric parameters to be well correlated in the temporal domain but reported only weak-to-moderate correlations between sub-segment pressures and intersegmental range of motion.…”
Section: Experimental Set-upmentioning
confidence: 99%